Categorical methods for the interpretation of RNA profiles as cell type evidence and their limitations. (December 2015) - de Zoete, Jacob; Curran, James; Sjerps, Marjan
Abstract: Existing methods for the interpretation of RNA profiles as evidence for the presence of certain cell types aim for making categorical statements. Such statements limit the possibility to report the associated uncertainty. From a statistical point of view, a probabilistic approach is a preferable choice. Here, four popular existing methods for the interpretation of RNA evidence are discussed.